Determinants of fertility decline in India : an analysis - Zachariah, K. C.; Patel, Sulekha (Washington, D.C., U.S.A. : World Bank, 1984)
"Fertility Transition in South India" documents the various phases of fertility transition in India. It argues that this transition is best understood as the cumulative effect of behavioural changes - such as delay in marriage and use of contraceptives - which over time has altered social perceptions on fertility.
Includes bibliographical references.
aia 22/09/2016
Loans
Keywords: Fertility, Human; Birth control; India